(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2025)
The escalating global environmental crisis—including deforestation, plastic pollution, and the overexploitation of natural resources—demonstrates that technical approaches alone are insufficient. Seyyed Hossein Nasr, a contemporary Islamic philosopher, offers an alternative perspective through the concept of scientia sacra, viewing the ecological crisis as a manifestation of a deeper spiritual crisis in modern humanity. This study aims to analyze Nasr’s thoughts on environmental ethics and their relevance to sustainable natural resource management. This research employs a qualitative library research method, using documentation techniques and content analysis of Nasr’s key works, such as Man and Nature and Religion and the Order of Nature. The findings reveal that Nasr constructs an environmental ethics framework rooted in ecological theocentrism, placing God at the center of the human–nature relationship. In this view, humans as khalifah bear a spiritual responsibility to protect nature and restore its sacredness. This concept is especially relevant in the Indonesian context, encouraging the integration of ethical and spiritual values into policy, education, and ecological awareness.